2022
DOI: 10.1111/pce.14342
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide association study revealed TaHXK3‐2A as a candidate gene controlling stomatal index in wheat seedlings

Abstract: Stomata are important channels for the control of gas exchange between plants and the atmosphere. To examine the genetic architecture of wheat stomatal index, we performed a genome-wide association study (GWAS) using a panel of 539 wheat accessions and 450 678 polymorphic single nucleotide polymorphisms (SNPs) that were detected using wheat-specific 660K SNP array. A total of 130 SNPs were detected to be significantly associated with stomatal index in both leaf surfaces of wheat seedlings. These significant SN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 82 publications
1
7
0
Order By: Relevance
“…There is the presence of paracytic stomata on both abaxial and adaxial surfaces of the leaf, however higher stomatal density was observed on the abaxial surface [ 4 ]. Interestingly, the stomatal density is also regulated by various genes and have been reported in other crops too [ 44 , 45 , 46 ]. Being sciophytic this plant shows high nitrogen content/leaf area, high leaf mass/leaf area unit, thicker leaves having higher respiration rate and chloroplasts under full irradiance compared to net shade plants [ 47 ].…”
Section: Diversity and Variationsmentioning
confidence: 87%
“…There is the presence of paracytic stomata on both abaxial and adaxial surfaces of the leaf, however higher stomatal density was observed on the abaxial surface [ 4 ]. Interestingly, the stomatal density is also regulated by various genes and have been reported in other crops too [ 44 , 45 , 46 ]. Being sciophytic this plant shows high nitrogen content/leaf area, high leaf mass/leaf area unit, thicker leaves having higher respiration rate and chloroplasts under full irradiance compared to net shade plants [ 47 ].…”
Section: Diversity and Variationsmentioning
confidence: 87%
“…Mao et al (2020) found that a 3 bp insertion in the TaSNAC8‐6A promoter increased the transcription of TaSNAC8‐6A to enhance drought tolerance. In turn, promoter variation of TaNAC071‐A and TaHXK3‐2A also found to elicit the transcription of target genes, thereby contributing to the regulation of responses to drought stress (Li et al, 2022; Mao et al, 2022). In this study, we found two types of promoters, TaSINA2B I and TaSINA2B II , from 192 wheat accessions (Figure 2a).…”
Section: Discussionmentioning
confidence: 99%
“…Besides SR, the degrees of leaf rolling and wilting, stomatal size and density, and root architecture are important traits which contribute to drought resistance (Krannich et al, 2015; Caine et al, 2019; Dunn et al, 2019; Li et al, 2022). DROUGHT1 ( DROT1 ), encoding a COBRA‐like protein, was identified in a GWAS in rice based on an index combining the degree of leaf rolling with the color of seedling leaves under drought conditions (Sun et al, 2022b).…”
Section: Advances In the Genetic Dissection Of Drought Resistance In ...mentioning
confidence: 99%